REPORT OF THE COMMITTEE ON COST CONCEPTS AND STANDARDS. - Lafferty, George W.; Matz, Adolph; Ostlund, Harry J.; Vincent, Vern; Benninger, Lawrence J. (The Accounting Review, 1952)
Abstract The Executive Committee of the American Accounting Association reactivated the committee on cost concepts and standards for the year 1951. The Executive Committee hoped that in reestablishing this Committee, the groundwork laid by previous committees would be carried forward to the benefit of the Association and the profession of accounting as a whole. The 1951 Committee made an intensive exploratory study of the possibility of setting forth principles, concepts and standards of accounting. As an approach to offering positive guidance to current cost accounting problems, the Committee felt that this afforded the best opportunity to be of service at the present time. As a consequence, major stress of the 1951 Committee is upon cost concepts and related business decisions and policy and, to a lesser extent, upon principles or standards of cost accounting. Cost accounting is a tool of management. In so far as it aids management in the preparation of general financial statements, it supplies data, which may be used eventually as a guide to the overall efficiency of an organization, the relative efficiency of a firm to other firms in an industry, or the relative profitableness of present pursuits of management as contrasted to alternative opportunities.